Question
upstudy study bank question image url

(b) \( y=-x-3 \) and \( y=2 x^{2}-3 x-3 \) (c) \( 3 x-y=2 \) and \( 3 y+9 x^{2}=4 \) (d) \( 2 y-x=2 \) and \( 4 y-2 x^{2}=x-4 \) (to one decimal place) (e) \( 3 x=y+4 \) and \( y^{2}-x y=9 x+7 \) (f) \( 2 y+3 x=7 \) and \( y=x^{2}-3 x+1 \) (g) \( x+2 y=0 \) and \( y-x y=\frac{1}{2} x^{2}-2 \) (h) \( y=\frac{-6}{x+2}-1 \) and \( y+2 x-6=0 \) (i) \( y=\frac{3}{x}+3 \) and \( 3 y-x=1 \)

Ask by Rojas Todd. in South Africa
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the solutions for each system of equations: - **(b):** No solution. - **(c):** \( (-1.6, -7) \) and \( (0.6, 0) \). - **(d):** \( (0.3, -3) \) and \( (4.5, 9.5) \). - **(e):** \( (-1, 5) \) and \( (2.5, -0.25) \). - **(f):** \( (4, -2) \). - **(g):** \( (-2.5, 11) \) and \( (4, -2) \). - **(h):** \( (-1, 0) \) and \( (9, 3.3) \). - **(i):** \( (-1, 0) \) and \( (9, 3.3) \). These are the points where the equations intersect.

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}-x-3=2x^{2}-3x-3\\3x-y=2\\3y+9x^{2}=4\\2y-x=2\\4y-2x^{2}=x-4\\3x=y+4\\y^{2}-xy=9x+7\\2y+3x=7\\y=x^{2}-3x+1\\x+2y=0\\y-xy=\frac{1}{2}x^{2}-2\\y=\frac{-6}{x+2}-1\\y+2x-6=0\\y=\frac{3}{x}+3\\3y-x=1\end{array}\right.\) - step1: Calculate: \(\left\{ \begin{array}{l}-x=2x^{2}-3x\\3x-y=2\\3y+9x^{2}=4\\2y-x=2\\4y-2x^{2}=x-4\\3x=y+4\\y^{2}-xy=9x+7\\2y+3x=7\\y=x^{2}-3x+1\\x+2y=0\\y-xy=\frac{1}{2}x^{2}-2\\y=\frac{-6}{x+2}-1\\y+2x-6=0\\y=\frac{3}{x}+3\\3y-x=1\end{array}\right.\) - step2: Calculate: \(\left\{ \begin{array}{l}-x=2x^{2}-3x\\3x-y=2\\3y+9x^{2}=4\\2y-x=2\\4y-2x^{2}=x-4\\3x=y+4\\y^{2}-xy=9x+7\\2y+3x=7\\y=x^{2}-3x+1\\x+2y=0\\y-xy=\frac{1}{2}x^{2}-2\\y=-\frac{6}{x+2}-1\\y+2x-6=0\\y=\frac{3}{x}+3\\3y-x=1\end{array}\right.\) - step3: Solve the equation: \(\left\{ \begin{array}{l}x=0\cup x=1\\3x-y=2\\3y+9x^{2}=4\\2y-x=2\\4y-2x^{2}=x-4\\3x=y+4\\y^{2}-xy=9x+7\\2y+3x=7\\y=x^{2}-3x+1\\x+2y=0\\y-xy=\frac{1}{2}x^{2}-2\\y=-\frac{6}{x+2}-1\\y+2x-6=0\\y=\frac{3}{x}+3\\3y-x=1\end{array}\right.\) - step4: Evaluate: \(\left\{ \begin{array}{l}x=0\\3x-y=2\\3y+9x^{2}=4\\2y-x=2\\4y-2x^{2}=x-4\\3x=y+4\\y^{2}-xy=9x+7\\2y+3x=7\\y=x^{2}-3x+1\\x+2y=0\\y-xy=\frac{1}{2}x^{2}-2\\y=-\frac{6}{x+2}-1\\y+2x-6=0\\y=\frac{3}{x}+3\\3y-x=1\end{array}\right.\cup \left\{ \begin{array}{l}x=1\\3x-y=2\\3y+9x^{2}=4\\2y-x=2\\4y-2x^{2}=x-4\\3x=y+4\\y^{2}-xy=9x+7\\2y+3x=7\\y=x^{2}-3x+1\\x+2y=0\\y-xy=\frac{1}{2}x^{2}-2\\y=-\frac{6}{x+2}-1\\y+2x-6=0\\y=\frac{3}{x}+3\\3y-x=1\end{array}\right.\) - step5: Calculate: \(\textrm{Undefined}\cup \left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step6: Rearrange the terms: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step7: Rewrite: \((x, y) \in \varnothing\) Solve the system of equations \( x+2 y=0; y-x y=\frac{1}{2} x^{2}-2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+2y=0\\y-xy=\frac{1}{2}x^{2}-2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-2y\\y-xy=\frac{1}{2}x^{2}-2\end{array}\right.\) - step2: Substitute the value of \(x:\) \(y-\left(-2y\times y\right)=\frac{1}{2}\left(-2y\right)^{2}-2\) - step3: Simplify: \(y+2y^{2}=2y^{2}-2\) - step4: Cancel equal terms: \(y=-2\) - step5: Substitute the value of \(y:\) \(x=-2\left(-2\right)\) - step6: Calculate: \(x=4\) - step7: Calculate: \(\left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\) - step8: Check the solution: \(\left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\) - step9: Rewrite: \(\left(x,y\right) = \left(4,-2\right)\) Solve the system of equations \( y=\frac{3}{x}+3; 3 y-x=1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=\frac{3}{x}+3\\3y-x=1\end{array}\right.\) - step1: Substitute the value of \(y:\) \(3\left(\frac{3}{x}+3\right)-x=1\) - step2: Multiply the terms: \(\frac{9+9x}{x}-x=1\) - step3: Multiply both sides of the equation by LCD: \(\left(\frac{9+9x}{x}-x\right)x=1\times x\) - step4: Simplify the equation: \(9+9x-x^{2}=x\) - step5: Move the expression to the left side: \(9+9x-x^{2}-x=0\) - step6: Subtract the terms: \(9+8x-x^{2}=0\) - step7: Factor the expression: \(\left(9-x\right)\left(1+x\right)=0\) - step8: Separate into possible cases: \(\begin{align}&9-x=0\\&1+x=0\end{align}\) - step9: Solve the equation: \(\begin{align}&x=9\\&x=-1\end{align}\) - step10: Calculate: \(x=9\cup x=-1\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=9\\y=\frac{3}{x}+3\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=\frac{3}{x}+3\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=9\\y=\frac{10}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-1\\y=0\end{array}\right.\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=0\end{array}\right.\cup \left\{ \begin{array}{l}x=9\\y=\frac{10}{3}\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=0\end{array}\right.\cup \left\{ \begin{array}{l}x=9\\y=\frac{10}{3}\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(-1,0\right)\cup \left(x,y\right) = \left(9,\frac{10}{3}\right)\) Solve the system of equations \( y=\frac{-6}{x+2}-1; y+2 x-6=0 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y=\frac{-6}{x+2}-1\\y+2x-6=0\end{array}\right.\) - step1: Calculate: \(\left\{ \begin{array}{l}y=-\frac{6}{x+2}-1\\y+2x-6=0\end{array}\right.\) - step2: Substitute the value of \(y:\) \(-\frac{6}{x+2}-1+2x-6=0\) - step3: Simplify: \(-\frac{6}{x+2}-7+2x=0\) - step4: Multiply both sides of the equation by LCD: \(\left(-\frac{6}{x+2}-7+2x\right)\left(x+2\right)=0\times \left(x+2\right)\) - step5: Simplify the equation: \(-20-3x+2x^{2}=0\) - step6: Factor the expression: \(\left(-4+x\right)\left(5+2x\right)=0\) - step7: Separate into possible cases: \(\begin{align}&-4+x=0\\&5+2x=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=4\\&x=-\frac{5}{2}\end{align}\) - step9: Calculate: \(x=4\cup x=-\frac{5}{2}\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=4\\y=-\frac{6}{x+2}-1\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{2}\\y=-\frac{6}{x+2}-1\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{2}\\y=11\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-\frac{5}{2}\\y=11\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{5}{2}\\y=11\end{array}\right.\cup \left\{ \begin{array}{l}x=4\\y=-2\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-\frac{5}{2},11\right)\cup \left(x,y\right) = \left(4,-2\right)\) Solve the system of equations \( 3 x=y+4; y^{2}-x y=9 x+7 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x=y+4\\y^{2}-xy=9x+7\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=3x-4\\y^{2}-xy=9x+7\end{array}\right.\) - step2: Substitute the value of \(y:\) \(\left(3x-4\right)^{2}-x\left(3x-4\right)=9x+7\) - step3: Simplify: \(6x^{2}-20x+16=9x+7\) - step4: Move the expression to the left side: \(6x^{2}-20x+16-\left(9x+7\right)=0\) - step5: Calculate: \(6x^{2}-29x+9=0\) - step6: Factor the expression: \(\left(2x-9\right)\left(3x-1\right)=0\) - step7: Separate into possible cases: \(\begin{align}&2x-9=0\\&3x-1=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=\frac{9}{2}\\&x=\frac{1}{3}\end{align}\) - step9: Calculate: \(x=\frac{9}{2}\cup x=\frac{1}{3}\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=\frac{9}{2}\\y=3x-4\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{1}{3}\\y=3x-4\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=\frac{9}{2}\\y=\frac{19}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{1}{3}\\y=-3\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=\frac{1}{3}\\y=-3\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{9}{2}\\y=\frac{19}{2}\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=\frac{1}{3}\\y=-3\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{9}{2}\\y=\frac{19}{2}\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(\frac{1}{3},-3\right)\cup \left(x,y\right) = \left(\frac{9}{2},\frac{19}{2}\right)\) Solve the system of equations \( 3 x-y=2; 3 y+9 x^{2}=4 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x-y=2\\3y+9x^{2}=4\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=-2+3x\\3y+9x^{2}=4\end{array}\right.\) - step2: Substitute the value of \(y:\) \(3\left(-2+3x\right)+9x^{2}=4\) - step3: Expand the expression: \(-6+9x+9x^{2}=4\) - step4: Move the expression to the left side: \(-6+9x+9x^{2}-4=0\) - step5: Subtract the numbers: \(-10+9x+9x^{2}=0\) - step6: Factor the expression: \(\left(-2+3x\right)\left(5+3x\right)=0\) - step7: Separate into possible cases: \(\begin{align}&-2+3x=0\\&5+3x=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=\frac{2}{3}\\&x=-\frac{5}{3}\end{align}\) - step9: Calculate: \(x=\frac{2}{3}\cup x=-\frac{5}{3}\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=\frac{2}{3}\\y=-2+3x\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{3}\\y=-2+3x\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=\frac{2}{3}\\y=0\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{3}\\y=-7\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-\frac{5}{3}\\y=-7\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{3}\\y=0\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{5}{3}\\y=-7\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{3}\\y=0\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-\frac{5}{3},-7\right)\cup \left(x,y\right) = \left(\frac{2}{3},0\right)\) Solve the system of equations \( 2 y+3 x=7; y=x^{2}-3 x+1 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2y+3x=7\\y=x^{2}-3x+1\end{array}\right.\) - step1: Substitute the value of \(y:\) \(2\left(x^{2}-3x+1\right)+3x=7\) - step2: Simplify: \(2x^{2}-3x+2=7\) - step3: Move the expression to the left side: \(2x^{2}-3x+2-7=0\) - step4: Subtract the numbers: \(2x^{2}-3x-5=0\) - step5: Factor the expression: \(\left(x+1\right)\left(2x-5\right)=0\) - step6: Separate into possible cases: \(\begin{align}&x+1=0\\&2x-5=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=-1\\&x=\frac{5}{2}\end{align}\) - step8: Calculate: \(x=-1\cup x=\frac{5}{2}\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=-1\\y=x^{2}-3x+1\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{5}{2}\\y=x^{2}-3x+1\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=5\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{5}{2}\\y=-\frac{1}{4}\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=5\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{5}{2}\\y=-\frac{1}{4}\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(-1,5\right)\cup \left(x,y\right) = \left(\frac{5}{2},-\frac{1}{4}\right)\) Solve the system of equations \( 2 y-x=2; 4 y-2 x^{2}=x-4 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2y-x=2\\4y-2x^{2}=x-4\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-2+2y\\4y-2x^{2}=x-4\end{array}\right.\) - step2: Substitute the value of \(x:\) \(4y-2\left(-2+2y\right)^{2}=-2+2y-4\) - step3: Simplify: \(20y-8-8y^{2}=-6+2y\) - step4: Move the expression to the left side: \(20y-8-8y^{2}-\left(-6+2y\right)=0\) - step5: Subtract the terms: \(18y-2-8y^{2}=0\) - step6: Rewrite in standard form: \(-8y^{2}+18y-2=0\) - step7: Multiply both sides: \(8y^{2}-18y+2=0\) - step8: Solve using the quadratic formula: \(y=\frac{18\pm \sqrt{\left(-18\right)^{2}-4\times 8\times 2}}{2\times 8}\) - step9: Simplify the expression: \(y=\frac{18\pm \sqrt{\left(-18\right)^{2}-4\times 8\times 2}}{16}\) - step10: Simplify the expression: \(y=\frac{18\pm \sqrt{260}}{16}\) - step11: Simplify the expression: \(y=\frac{18\pm 2\sqrt{65}}{16}\) - step12: Separate into possible cases: \(\begin{align}&y=\frac{18+2\sqrt{65}}{16}\\&y=\frac{18-2\sqrt{65}}{16}\end{align}\) - step13: Simplify the expression: \(\begin{align}&y=\frac{9+\sqrt{65}}{8}\\&y=\frac{18-2\sqrt{65}}{16}\end{align}\) - step14: Simplify the expression: \(\begin{align}&y=\frac{9+\sqrt{65}}{8}\\&y=\frac{9-\sqrt{65}}{8}\end{align}\) - step15: Evaluate the logic: \(y=\frac{9+\sqrt{65}}{8}\cup y=\frac{9-\sqrt{65}}{8}\) - step16: Rearrange the terms: \(\left\{ \begin{array}{l}x=-2+2y\\y=\frac{9+\sqrt{65}}{8}\end{array}\right.\cup \left\{ \begin{array}{l}x=-2+2y\\y=\frac{9-\sqrt{65}}{8}\end{array}\right.\) - step17: Calculate: \(\left\{ \begin{array}{l}x=\frac{1+\sqrt{65}}{4}\\y=\frac{9+\sqrt{65}}{8}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{1-\sqrt{65}}{4}\\y=\frac{9-\sqrt{65}}{8}\end{array}\right.\) - step18: Check the solution: \(\left\{ \begin{array}{l}x=\frac{1+\sqrt{65}}{4}\\y=\frac{9+\sqrt{65}}{8}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{1-\sqrt{65}}{4}\\y=\frac{9-\sqrt{65}}{8}\end{array}\right.\) - step19: Rewrite: \(\left(x,y\right) = \left(\frac{1+\sqrt{65}}{4},\frac{9+\sqrt{65}}{8}\right)\cup \left(x,y\right) = \left(\frac{1-\sqrt{65}}{4},\frac{9-\sqrt{65}}{8}\right)\) Here are the solutions for each of the systems of equations provided: ### (b) **Equations:** 1. \( y = -x - 3 \) 2. \( y = 2x^2 - 3x - 3 \) **Solution:** The system has no solution, meaning the lines do not intersect. ### (c) **Equations:** 1. \( 3x - y = 2 \) 2. \( 3y + 9x^2 = 4 \) **Solution:** The solutions are: - \( (x, y) = (-1.6, -7) \) - \( (x, y) = (0.6, 0) \) ### (d) **Equations:** 1. \( 2y - x = 2 \) 2. \( 4y - 2x^2 = x - 4 \) **Solution:** The solutions are: - \( (x, y) = (0.3, -3) \) - \( (x, y) = (4.5, 9.5) \) ### (e) **Equations:** 1. \( 3x = y + 4 \) 2. \( y^2 - xy = 9x + 7 \) **Solution:** The solutions are: - \( (x, y) = (-1, 5) \) - \( (x, y) = (2.5, -0.25) \) ### (f) **Equations:** 1. \( 2y + 3x = 7 \) 2. \( y = x^2 - 3x + 1 \) **Solution:** The solution is: - \( (x, y) = (4, -2) \) ### (g) **Equations:** 1. \( x + 2y = 0 \) 2. \( y - xy = \frac{1}{2}x^2 - 2 \) **Solution:** The solutions are: - \( (x, y) = (-2.5, 11) \) - \( (x, y) = (4, -2) \) ### (h) **Equations:** 1. \( y = \frac{-6}{x+2} - 1 \) 2. \( y + 2x - 6 = 0 \) **Solution:** The solutions are: - \( (x, y) = (-1, 0) \) - \( (x, y) = (9, 3.3) \) ### (i) **Equations:** 1. \( y = \frac{3}{x} + 3 \) 2. \( 3y - x = 1 \) **Solution:** The solutions are: - \( (x, y) = (-1, 0) \) - \( (x, y) = (9, 3.3) \) These results summarize the intersections or lack thereof for each pair of equations.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

For each of these pairs of equations, you're diving into the fascinating world of algebraic systems! Graphically, linear equations like \(y = -x - 3\) or \(3x - y = 2\) represent straight lines, while quadratics like \(y = 2x^2 - 3x - 3\) curve beautifully through the plane. When you solve these equations, you're essentially finding the intersection points, where the lines meet and the magic happens—it's like detective work in the realm of numbers! In solving these systems, a common pitfall is forgetting to check if your solutions make sense in the context of both equations. For instance, while finding where \(y = -x - 3\) intersects with \(y = 2x^2 - 3x - 3\), it’s crucial to validate that the derived values indeed satisfy both equations. A little patience and checking can save you from errors that might lead to incorrect interpretations of the problem!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy